Students of a Feather "Flocked" Together: A Group Assignment Method for Reducing Free-Riding and Improving Group and Individual Learning Outcomes. (August 2018) - Harding, Lora Mitchell
Group-based teaching and learning is ubiquitous across undergraduate and graduate business curricula, and with any type of group work, free-riding—a form of social loafing in which free-riding group members reap the rewards of nonloafing members without exerting comparable effort—is a concern. This research examines a group assignment method, herein called the flocking method, designed to reduce free-riding by improving students' motivation and availability to contribute to the group. A quasi-experiment is described in which students were flocked, or matched, according to their schedule availability and willingness to devote time to the course, such that motivated students (i.e., those who planned to devote more time) were grouped with other motivated students with similar schedules, whereas unmotivated students were grouped with other unmotivated students with similar schedules. Compared with self-selected groups, students in flocked groups not only reported less free-riding, they also performed better on group and individual assignments, indicating an actual reduction in free-riding. Additionally, compared with the most prominent methods for reducing free-riding examined in literature, the flocking method of group assignment reduces resource demands on the instructor and students, making it as efficient to implement as it is effective. Limitations and directions for future research are discussed.